(3fRgI GdYTGb hfgRI GdeSJGbs - (3YHO Gddg Hf eMeO Hf Ydj Hf GdMSf, CHh GdeYGdj Yjf GdbVGI GdgePGfj GdejGfLj,J (B525 (3g` s ((3eMeO Hf CHj SYjO GHf CHj efUhQ s)
(3ChdgG (B:s
(3CeG HYO MeO ddg JYGdi(B: (3abO cfJ hENhGJj HgePGf fJfGTO afhf GdTYQ s
(3BNQgG (B:s
(3aeG RGd Yfg Gddbe MJi cCfg ef GdYj deG Cf Jcde HCbod s
(3GdNW ajg HYV GdVHWs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B132 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B455s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B145 s
Keywords: (3GdCOHs